THE SEMANTICS OF THE COLOR “RED” IN ENGLISH AND UZBEK AND ITS GRADUAL DEVELOPMENT (Global Conference on Multidisciplinary Research and Innovation, 2026)
This research paper explores the multifaceted semantic landscape of the color "red" through a comparative analysis of the English and Uzbek languages. The study focuses on the gradual development of the color’s meaning, tracing its evolution from a primary sensory perception to a complex system of cultural, emotional, and ideological metaphors. By examining the lexical-semantic fields of "red" and "qizil," (in uzbek) the author identifies the specific historical and social factors that have shaped their distinct paths of growth. The investigation reveals that while both languages share a biological foundation for color perception, their idiomatic and metaphorical structures diverge based on unique national identities. In English, the development of "red" is closely linked to judicial, economic, and emotional archetypes, often representing warnings, financial status, or intense passions. Conversely, the Uzbek "qizil" demonstrates a deep-rooted connection to traditional rituals, health, and beauty, while also reflecting significant semantic shifts during the 20th-century political landscape.
Keywords: Comparative Linguistics, Color Semantics, Diachronic Analysis, English, Uzbek, Conceptual Metaphor, Ethnolinguistics, Lexical Evolution.